Teoria de decisão e acidentes de trabalho: Variação da “utilidade negativa” de prejuízos corporais em função do desenvolvimento industrial - Stephaneck, P.; Donadi, D. C. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The use of a psychometric function relating estimated values to observed values on a “confusion” scale made possible the establishment of negative utilities associated with bodily injury in the work situation. Ss compared events representing losses. Both quantifiable (material losses) and non-quantifiable (bodily injury) items were included. The variation of the negative utilities of these loss-events among workers of two different social contexts were examined in terms of industrial development. Almost identical logarithmic utility scales were found to obtain for the two population samples studied with respect to quantifiable items. On the other hand, the values associated with bodily injury were clearly different for the two groups. Negative utilities for accidents were considerably higher in the highly industrialized context. Results strongly suggest that subjective values associated with health and physical integrity may well evolve alongside social and economic progress. The utilization of methods analogous to the one described is recommended as a viable means for establishing the parameters of the curve representing the proposed evolutionary process.